Integration of Career Guidance, Career Development, and Vocational High School Curriculum to Improve the Quality of Graduates Ready for Work - Arik Harianto; Buwani Buwani; Erta Faradina; Tuwoso Tuwoso (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze the integration between career guidance, career development, and the curriculum of Vocational High Schools (SMK) in an effort to improve the quality of graduates who are ready to work. Through a descriptive qualitative approach, data were collected from various literature sources and previous research. The results of the analysis indicate that the synergy between career guidance, career development, and relevant curriculum can improve the competence and work readiness of SMK graduates. The implementation of a structured career guidance program, the development of an industry-based curriculum, and collaboration with the business world/industry (DUDI) are the keys to achieving these goals.